Enhanced Photocatalysis of Reduced Graphene Oxide-CuS Nanostructures - He, H.-Y. (Recent Patents on Materials Science, 2017)
Background: Heterojunction interface effect and wide light absorption are attracting many attentions for environmental application. Reduced Graphene Oxide (RGO)/semiconductor hybrids have showed very high photocatalytic activity than single one. RGO/CuS hybrids should be a competitive material with highly photocatalytic activity. Objective: This work focused on the synthesis and photocatalytic activity of the CuS nanoparticles composited with Reduced Graphene Oxide (RGO) and the roles of various operation parameters on the photocatalyric activity of the hybrids. Method: The RGO/CuS nanohybrids were synthesized by chemical solution reaction and characterized by various techniques to understand microstructural, physchemical, and photocatalytic properties. Results: The CuS nanocrystallines were uniform combined on the RGO surface. The CuS nanoparticles showed narrow bandgap that further narrowed as increasing rGO/CuS ratio. The CuS nanopartiles showed excellent photocatalytic activities. Incorporating RGO further enhanced the activities. Moreover, the increase in RGO/CuS ratio and decrease in initial solution pH also enhanced the activities. The higher activities of the hybrids were ascribed to the good carrier transfer at heterojunction interface that was confirmed by band energy level calculation and visible photoluminescence weakened with increasing RGO/CuS. The present article discussed some important patents related to CuS and its hybrids materials. Conclusion: RGO/CuS nanohybrids are promising photocatalytic materials in application of environmental decontamination.
Keywords: interface effect